ROLE OF CLIPPING MANAGEMENT IN RESILIENCE PERFORMANCE OF BARLEY (Hordeum vulgare L.) VARIETIES IN CENTRAL PUNJAB - BALWINDER SINGH DHILLON (The Bioscan, 2021)
The performance of three barley varieties (DWRUB 52, PL 807 and PL 426) under five different clipping management practices control, clipping at 50 days after sowing (DAS), clipping at 60 DAS, clipping at 50 DAS + 0.5% Zn foliar application at anthesis and early milk stage (Zn (s) and clipping at 60 DAS + 0.5% Zn foliar application at anthesis and early milk stage (Zn (s) were recorded. Variety DWRUB 52 gave highest plant height (95.5 and 98.8 cm) and leaf area index (4.62 and 4.78) at harvest during 1st and 2nd year of study, respectively. Zn spray at anthesis and early milk stage with clipping at 50 and 60 DAS increased the plant height (93.2 and 91.5 cm), leaf area index (4.56 and 4.47) and chlorophyll index (46.1 and 44.7) of crop at maturity. There was an increase of 11.6% in grain yield when clipping was done at 50 DAS (38.8 and 40.9 q ha -1 ) with Zn spray and an increase of 7.8% in grain yield when clipping was done at 60 DAS (37.6 and 39.5 q ha -1 ) with Zn spray than control crop (34.5 and 36.3 q ha -1 ) during 1st and 2nd year of study, respectively.